PSYCHOLOGICAL ASPECTS OF THE COGNITIVE DEVELOPMENT OF SCHOOL STUDENTS IN THE MODERN EDUCATIONAL PROCESS (Universal International Scientific Journal, 2026)
This article examines the psychological aspects of school students’ cognitivedevelopment in the modern educational process. Cognitive development is considered as a processrelated to the formation and development of students’ cognitive processes such as sensation,perception, attention, memory, thinking, and imagination. The article highlights the influence ofthe educational environment, innovative pedagogical technologies, and teachers’ activities onstudents’ intellectual development. It also explains the importance of psychological factors indeveloping students’ independent thinking, problem-solving skills, and creative thinking. Theresults of the study show the importance of supporting students’ cognitive development anddeveloping effective teaching strategies in the modern educational process.
Keywords: cognitive development; educational process; psychological aspects